(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: This article focuses on the process of transferring Health Services to Municipalities in a context of Decentralization of Health Care to the State Representation Councils and Province Executive Councils, where it aims to identify the barriers to the transfer of Health Services for all Municipalities in Mozambique since its approval and entry into force. However, the qualitative methodology was used through the technique of bibliographical review of books, articles, dissertations, which allowed to highlight the need to transfer or create the financial, human and material resources necessary to guarantee the viability of the services, once assumed by the municipalities. Likewise, it justifies the need for the Central Government to stop prioritizing its coordination through the OLE (provincial and district governments) only through this route, privileging the municipalities. Finally, it emphasizes the need to sign more memoranda of a binding nature so that the process of transferring health services can take place.